The Incidence of Anal Sphincter Ruptures and Risk Factors - Santoso, Budi I; Khusen, Denny (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To analyze the incidence of anal sphincter ruptures and to evaluate risk factors of obstetric anal sphincter ruptures in Dr. Cipto Mangunkusumo Hospital. Method: We reviewed 2009 vaginal deliveries based on the analysis of obstetric data base and patient records of our department during 2012. Cases and control subjects were chosen randomly and patientâs records were reviewed for the following variable: maternal age, parity, gestational age, labor induction, duration of 2nd stage labor, use of forceps, use of vacuum, use of episiotomy, birth weight, and presentation of the baby. Result: There were 91 (4.53%) anal sphincter ruptures during period of study (91 of 2009 patients). An univariate analysis of these 91 case and 91 randomly selected control subjects show that primiparity (p = .000), gestational age (p = .016), duration of second-stage labor (p = .000), forceps delivery (p = .000), vacuum delivery (p = .001), episiotomy (p = .000), and birth weight (p = .000) increased the risk for anal sphincter ruptures. In multivariate re-gression models, only 5 of the 10 predictor variables were significantly related to the likelihood of having a severe perineal trauma greater than second degree. Primiparity (p = .023; OR 2.74, 95% [CI], 1.15-6.51), forceps delivery (p = .000; OR 18.18, 95% [CI] 3.84-86.07), vacuum delivery (p = .005; OR 6.83, 95% [CI] 1.77-26.42), episiotomy (p = .015; OR 2.86, 95% [CI] 1.23-6.65), and birth weight (p = .000; OR 0.99, 95% [CI] 0.997-0.999). Conclusion: Damage of the anal sphincter resulting in a third- or fourth- degree perineal tear is a relatively rare but severe complication of vaginal delivery. We found that factors as sociated with anal sphincter ruptures were primiparity, forceps, vacuum, episiotomy and birth weight. [Indones J Obstet Gynecol 2016; 1: 31-36] Keywords: anal sphincter ruptures, third- or fourth- degree perineal tear, vaginal delivery